Genetic Relationship Between Gembrong Goat, Kacang Goat and Kacang X Etawah Crossbred (PE) Based on Their Mitochondrial DNA - Lanang Oka, I Gusti; SayangYupardhi, Wayan; Mantra, Ida Bagus; Suyasa, Nyoman; Dewi, Anak Agung Sagung (Jurnal Veteriner; Vol 12, No 3 (2011))
Gembrong goat is a specific type of goat which has long hair covers its whole body including its neckand face, originated from eastern part of Bali (Karangasem). A study of this type of goat and its relationshipwith other local goats (Kacang and Kacang x Etawah crossbred) was carried out at Sawe village, Jembrana,Bali.. A number of 12 gembrong goats, 3 kacang goats from Kubu village, Karangasem and 3 Kacang xEtawah crossbred goats from Denpasar were used in this study. Blood samples of all goats were collectedfor mitochondrial DNA (mtDNA) analysis. PCR amplification of D-loop mitochondrial DNA was carriedout by using two primers i.e. CAP-F (5’-CGTGTATGCAAGTACATTAC -3’) and CAP-R (5’-CTGATTAGTCATTAGTCCATC – 3’) . Sequencing of 550 bp (base-pairs) of mitochondrial DNA (productof PCR) only found one polymorphic site at base number 231 with two haplotypes in gembrong goat only,while the other base-pairs were similar between the three goat types (Gembrong, Kacang and Kacang xEtawah crossbred) .The frequency of haplotype 1 was 83.3% and the frequency of haplotype 2 was 16.7%.It was concluded that based on their mitochondrial DNA sequences and “phylogenic analysis”, the threetypes of goat (Gembrong,Kacang and Kacang xEtawah crossbred) had a very close genetic relationship(kinship).
Keywords: Gembrong goat, mitochondrial DNA, genetic relationship